A New Family of Renewable Thermosets: Kraft Lignin Poly‐adipates. Issue 11 (29th April 2022) - Di Francesco, Davide; Rigo, Davide; Reddy Baddigam, Kiran; Mathew, Aji P.; Hedin, Niklas; Selva, Maurizio; Samec, Joseph S. M.
Abstract: Thermosetting polymeric materials have advantageous properties and are therefore used in numerous applications. In this study, it was hypothesized and ultimately shown that thermosets could be derived from comparably sustainable sub‐components. A two‐step procedure to produce a thermoset comprising of Kraft lignin (KL) and the cross‐linker adipic acid (AdA) was developed. The cross‐linking was activated by means of an acetylating agent comprising isopropenyl acetate (IPA) to form a cross‐linking mixture (CLM). The cross‐linking was confirmed by FTIR and solid‐state NMR spectroscopy, and the esterification reactions were further studied using model compounds. When the KL lignin was mixed with the CLM, partial esterification occurred to yield a homogeneous viscous liquid that could easily be poured into a mold, as the first step in the procedure. Without any additions, the mold was heated and the material transformed into a thermoset by reaction of the two carboxylic acid‐derivatives of AdA and KL in the second step. Abstract : Renewable thermoset : Kraft lignin, a by‐product from the paper and pulp industry is mixed with a cross‐linking mixture based on adipic acid able to react with lignin under heat. The resulting material is a partially esterified mixture with thermoplastic‐like properties. Such a liquid can undergo further thermal treatment inside a mold under pressure to yield a tunable thermoset without any additives.